Handbook of plant-based fermented food and beverage technology - Hui, Y. H. (Yiu H.); Evranuz, E. Ozgul (Boca Raton, FL : CRC Press, 2012)
'This second edition of a bestseller examines a wide range of starter cultures and manufacturing procedures for popular plant-based food products. The text focuses on the quality of the final food product, flavor formation and new advances in starter cultures for dairy fermentations using recent examples that depict the main species used, their characteristics, and their impact on the development of other fermented foods. Also new to the second edition: sections on fermented fruit such as apple cider, fermented specialties such as vanilla, and U.S. permitted food ingredients derived each fermented product. '--
'This second edition of a bestseller examines a wide range of starter cultures and manufacturing procedures for popular plant-based food products. The text focuses on the quality of the final food product, flavor formation and new advances in starter cultures for dairy fermentations using recent examples that depict the main species used, their characteristics, and their impact on the development of other fermented foods. Also new to the second edition: sections on fermented fruit such as apple cider, fermented specialties such as vanilla, and U.S. permitted food ingredients derived each fermented product. Covers numerous fermentation procedures by reviewing the type of raw material used, its pretreatment, the temperature/climate, and the conditions of the fermentation process. Discusses various types of starter cultures and their preparation prior to use. Outlines some of the flaws that may be found in sour cream products, their causes, and possible ways to prevent these defects. Analyzes the sensory characteristics of various fermented food products including texture, color, and aroma'--
Rev. ed. of: Handbook of food and beverage fermentation technology / edited by Y.H. Hui ... [et al.]. 2004.
'Handbook of food and beverage fermentation technology' is the first edition of'Handbook of plant-based fermented food and beverage technology' and'Handbook of animal-based fermented food and beverage technology.'
Includes bibliographical references and an index.
Keywords: Fermented foods -- Handbooks, manuals, etc; Beverages -- Microbiology -- Handbooks, manuals, etc; Fermentation -- Handbooks, manuals, etc; Plant proteins as food -- Handbooks, manuals, etc; Plant products -- Handbooks, manuals, etc